Visual studies a skeptical introduction - Elkins, James 1955- (Routledge, 2003)
"Visual studies is a rapidly expanding intellectual field, growing throughout colleges and universities around the world. But is it asking the most interesting questions? And is it just too easy to do? In his latest book, James Elkins offers a road map through the field of visual studies, describing its major concerns and its principal theoretical sources. Then, with the skill and insight that have marked his successful books on art and visuality, Elkins takes the reader down a side road where visual studies can become a more interesting place. Why look only at the same handful of theorists? Why exclude from one's field of vision non-Western art or the wealth of scientific images? The centerpiece of Visual Studies is Elkins's proposal for ten ways in which visual studies could be made more difficult - theoretically, practically, and in terms of its interpretative and historical range. As Stories of Art offered an antidote to the authorized version of art history, Visual Studies: A Skeptical Introduction proposes a refreshingly open-minded introduction to a growing field. This handsome volume is illustrated throughout." http://www.loc.gov/catdir/enhancements/fy0651/2003013585-d.html.
Keywords: Art et société; Beeldcommunicatie; Beeldcultuur; Communication et culture; Communication visuelle; Onderzoek; Perception visuelle; Éducation visuelle; Art and society; Communication and culture; Culture; Visual communication; Visual literacy; Visual perception; Kulturwissenschaften; Visuelle Kommunikation; Kunstsoziologie; Kunstwissenschaft; Visuelle Wahrnehmung; Methode